The Influence of Learning Experience, Student Satisfaction and Loyalty on Word of Mouth and The Decision of Choosing a Private College - Muthia Fadila Puteri (PT SOLUSI EDUKASI BERDIKARI, 2024)
This research aims to test and analyze the influence of course experience, satisfaction and loyalty student on word of mouth and the college decision. The research approach used in this research is quantitative. This collection technique in this research was by distributing questionnaires online via google form to 135 respondents. The method used in this research is PLS-SEM using SmartPLS software. The results of this research are that student course experiences have a positive and significant effect on word of mouth, student satisfaction has a positive and significant effect on word of mouth, student loyalty does not have a positive and significant effect on word of mouth and word of mouth has a positive effect on college decisions.